National Revenue Administration – current organisational and financial problems - Ireneusz Nowak (Prawo Budżetowe Państwa i Samorządu)
The article is devoted to current problems related to the functioning of the National Tax Administration, at the same time relating to the ratio legis of that institution, but also regarding the education of its employees and officers of the Customs and Revenue Service. The Author of the article formulated in this respect both de lege lata and de lege ferenda postulates, using for this purpose, among others empirical material derived from information obtained from the Minister of Finance, the Head of the National Revenue Administration, the Director of the Bureau of the Domestic Fiscal Information, Directors of a Fiscal Administration Chambers, but also from parliamentary interpellations.